Market Risk Measures Impact on Systemic Risk in Indonesia Banking Industry - Surya Gustanto, Jodi; Rokhim, Rofikoh (Dinasti Publisher, 2024)
This study investigates the relationship between market risk measures and systemic risk in Indonesia's banking sector. It aims to inform policymakers and regulators in promoting financial stability. By examining how market risk measures, specifically total risk encompassing systematic and idiosyncratic components, influence systemic risk in Indonesia's banking system, this study addresses a notable research gap, particularly in emerging markets like Indonesia. This research contributes to the understanding of systemic risk dynamics in an emerging market context, offering insights into how market risk measures contribute to systemic risk. Employing a quantitative approach, this study utilizes secondary data from the Indonesia Stock Exchange and Datastream Refinitiv Eikon. Non-probability sampling selects banks listed on the Indonesia Stock Exchange, with daily stock price data used to construct market risk measures. Systemic risk is measured using both CoVaR and MES, and regression analysis is employed to explore the relationship between market risk and systemic risk. The study reveals a significant positive association between total risk and systemic risk, highlighting the crucial role of idiosyncratic risk in this relationship. These findings underscore the importance of considering both systematic and idiosyncratic market risk when assessing systemic risk in Indonesia's banking sector. The study emphasizes the need for robust risk management practices and regulatory measures to ensure financial stability in emerging markets.